The stolen gold affair [large type] - Pronzini, Bill (Muller, Marcia. Carpenter and Quincannon mystery., 2020)
In response to a string of gold thefts in a Mother Lode mine, former Secret Service agent John Quincannon goes undercover as a newly hired miner to identify and capture the men responsible. Meanwhile, Sabina Carpenter finds herself not only making plans for her and Quincannon's wedding, but also investigating both an audacious real estate scam and an abusive young man's villainous secret.